1997
DOI: 10.1038/ng0197-21
|View full text |Cite
|
Sign up to set email alerts
|

Holt-Oram syndrome is caused by mutations in TBX5, a member of the Brachyury (T) gene family

Abstract: Holt-Oram syndrome is a developmental disorder affecting the heart and upper limb, the gene for which was mapped to chromosome 12 two years ago. We have now identified a gene for this disorder (HOS1). The gene (TBX5) is a member of the Brachyury (T) family corresponding to the mouse Tbx5 gene. We have identified six mutations, three in HOS families and three in sporadic HOS cases. Each of the mutations introduces a premature stop codon in the TBX5 gene product. Tissue in situ hybridization studies on human emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
139
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 825 publications
(146 citation statements)
references
References 75 publications
1
139
0
3
Order By: Relevance
“…The existence of several human congenital syndromes caused by disruption of human TBX genes, demonstrates their importance in morphogenesis. The Holt-Oram syndrome is caused by TBX5 haploinsufficiency and is characterized by heart and hand anomalies [2]. Mutations in TBX1 have been implicated in the Velocardiofacial or DiGeorge syndrome in which congenital heart defects are present [3].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of several human congenital syndromes caused by disruption of human TBX genes, demonstrates their importance in morphogenesis. The Holt-Oram syndrome is caused by TBX5 haploinsufficiency and is characterized by heart and hand anomalies [2]. Mutations in TBX1 have been implicated in the Velocardiofacial or DiGeorge syndrome in which congenital heart defects are present [3].…”
Section: Introductionmentioning
confidence: 99%
“…TBR1 is of particular interest, because it encodes a neuron-specific transcription factor of the T-box family. T-box proteins have diverse biological roles 9 and haploinsufficiency of this class of regulatory protein has already been established as a cause of human disease 10 —for instance, ulnar-mammary syndrome and Holt–Oram syndrome are caused by haploinsufficiency of TBX3 and TBX5 , respectively 1113 . TBR1 has established roles in patterning of the central nervous system, including regulation of neuronal identities during cortical development 14 .…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that genetic factors contribute to the persistence of PFO and other defects of atrial septation, including atrial septal defects (ASD) [9], [10], [11]. A number of studies have shown that ASD exhibits autosomal dominant inheritance, and a list of causative genes encoding cardiac transcription factors and their targets ( NKX2-5 [12], TBX5 [13], GATA4 [10], MYH6 [14], ACTC [15], TBX20 [16]) have been identified. Variation in these genes or their expression may contribute to the development of PFO.…”
Section: Introductionmentioning
confidence: 99%